Revisiting purpose and conceptualisation in the design of assessments of mathematics teachers' knowledge. Issue 2 (3rd May 2020) - Orrill, Chandra Hawley; Copur-Gencturk, Yasemin; Cohen, Allan; Templin, Jonathan
ABSTRACT: In this paper, we focus on the design of assessments of mathematics teachers' knowledge by emphasising the importance of identifying the purpose for the assessment, defining the specific construct to be measured, and considering the affordances of particular psychometric models on the development of assessments as well as how they are able to communicate learning or understanding. We add to the literature by providing illustrations of the interactions among these critical considerations in determining what inferences can be drawn from an assessment. We illustrate how the considerations shape assessments by discussing both existing and ongoing research projects. We feature discussion of two projects on which the authors of this paper are collaborating to demonstrate the affordances of attending to all three considerations in designing assessments of mathematics teachers' knowledge to provide readers with opportunities to see those considerations in use.